Predictability of orthodontic movement with orthodontic aligners: a retrospective study - Luca Lombardo; Angela Arreghini; Fabio Ramina; Luis T. Huanca Ghislanzoni; Giuseppe Siciliani (SpringerOpen, 2017)
Abstract Background The aim of this study was to evaluate the predictability of F22 aligners (Sweden & Martina, Due Carrare, Italy) in guiding teeth into the positions planned using digital orthodontic setup. Methods Sixteen adult patients (6 males and 10 females, mean age 28 years 7 months) were selected, and a total of 345 teeth were analysed. Pre-treatment, ideal post-treatment-as planned on digital setup-and real post-treatment models were analysed using VAM software (Vectra, Canfield Scientific, Fairfield, NJ, USA). Prescribed and real rotation, mesiodistal tip and vestibulolingual tip were calculated for each tooth and, subsequently, analysed by tooth type (right and left upper and lower incisors, canines, premolars and molars) to identify the mean error and accuracy of each type of movement achieved with the aligner with respect to those planned using the setup. Results The mean predictability of movements achieved using F22 aligners was 73.6%. Mesiodistal tipping showed the most predictability, at 82.5% with respect to the ideal; this was followed by vestibulolingual tipping (72.9%) and finally rotation (66.8%). In particular, mesiodistal tip on the upper molars and lower premolars were achieved with the most predictability (93.4 and 96.7%, respectively), while rotation on the lower canines was the least efficaciously achieved (54.2%). Conclusions Without the use of auxiliaries, orthodontic aligners are unable to achieve programmed movement with 100% predictability. In particular, although tipping movements were efficaciously achieved, especially at the molars and premolars, rotation of the lower canines was an extremely unpredictable movement.